Medical students’ motivational profile. Sancti Spíritus Medical Sciences University - Eduardo Veloso Pérez; Arturo Puga García; Ariadna Veloso Rodríguez; Liyipsi Abreu Martín; Rosa María Ramos Palmero; Gloria María Puga Madiedo (Medisur)
Foundation: The reasons for entering the university determine, to a large extent, the student's success in the selected career, and subsequently, their professional performance. Knowing the motivational profile of students allows us to accurately project psycho-pedagogical actions in order to modify it with a view to satisfy the social demands of the corresponding group. Objective: to characterize the new students’ motivational profile to the Medicine career. Methods: an observational, descriptive and cross-sectional study was carried out from January to December 2023, at the Sancti Spíritus Medical Sciences University. The Motivational Hierarchy test (Ten Wishes Technique) was used, which was applied between weeks three and four of the 2023 academic year to 99 students selected through clusters and probabilistic sampling. Results: the reasons related to personal satisfaction (34.3%) and professionalism (32.3%) were the most expressed by students; the least expressed were those linked to work and society (5.4%), only 51 of the 928 expressed. Conclusions: the first-year Medicine degree students in the 2023 academic year, at the Sancti Spíritus Medical Sciences University do not present a motivational profile that favors study, and therefore, good academic results.